2013
DOI: 10.1161/circresaha.113.301296
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory Stimuli Engage Brahma Related Gene 1 and Brahma in Endothelial Injury

Abstract: Rationale Endothelial dysfunction inflicted by inflammation is found in a host of cardiovascular pathologies. One hallmark event in this process is the aggregation and adhesion of leukocyte to the vessel wall mediated by the up-regulation of adhesion molecules (CAM) in endothelial cells at the transcriptional level. The epigenetic modulator(s) of CAM transactivation and its underlying pathophysiological relevance remain poorly defined. Objective Our goal was to determine the involvement of Brg1 and Brm in CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 45 publications
4
63
1
Order By: Relevance
“…22 Evidence is mounting that in stressed vascular endothelium, the epigenetic machinery can actively regulate transcription to modify endothelial function tailoring to the inputs by various pathological cues. [12][13][14]23,24 By means of paracrine and endocrine, these stress signals can be relayed from the endothelium to other parts of the cardiovascular system (eg, the heart) to trigger detrimental changes. In this report, we detail an epigenetically regulated pathway wherein the histone H3K4 methyltransferase SET1 activates endothelin-1 transcription in endothelial cells and contributes to the pathogenesis of cardiac hypertrophy in response to chronic Ang II treatment ( Figure 7M).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Evidence is mounting that in stressed vascular endothelium, the epigenetic machinery can actively regulate transcription to modify endothelial function tailoring to the inputs by various pathological cues. [12][13][14]23,24 By means of paracrine and endocrine, these stress signals can be relayed from the endothelium to other parts of the cardiovascular system (eg, the heart) to trigger detrimental changes. In this report, we detail an epigenetically regulated pathway wherein the histone H3K4 methyltransferase SET1 activates endothelin-1 transcription in endothelial cells and contributes to the pathogenesis of cardiac hypertrophy in response to chronic Ang II treatment ( Figure 7M).…”
Section: Discussionmentioning
confidence: 99%
“…In the meantime, SET1 was silenced by lentiviral delivery of an endothelial-specific vector carrying interfering RNA targeting SET1 as have been shown for other proteins previously. 13,14,21 Immunofluorescence staining suggested that SET1 expression was specifically suppressed in the vascular endothelium ( Figure Figure 6A) and protein ( Figure 6B) levels in Ang II-infused mice. Consequently, there was a decrease of H3K4Me3 levels on the endothelin-1 promoter in the lungs ( Figure 6C).…”
Section: Endothelial Set1 Is Necessary For Ang Ii-induced Cardiomyocymentioning
confidence: 99%
“…ChIP and re-ChIP assays were performed essentially as described before 48 with anti-MRTF-A, anti-p300 (Santa Cruz Biotechnology), anti-acetyl H3K9, anti-acetyl H3K18, anti-acetyl H3K27, anti-trimethyl H3K4 (EMD Millipore), or anti-WDR5 (Bethyl Laboratories). Precipitated genomic DNA was amplified by real-time PCR with the primers listed in Table 1.…”
Section: Chipmentioning
confidence: 99%
“…To further verify this cell model in vivo, we injected C57/BL6 mice with lentivirus carrying MRTF-A-targeting shRNA (Endo-shMRTF-A) under the influence of Tie2 gene promoter to specifically knockdown MRTF-A in the endothelium [22]. The Hannon laboratory was among the first to demonstrate that synthesis of shRNA can be driven by RNA polymerase II [23,24].…”
Section: Endothelial Mrtf-a Is Indispensible For Ang Ii-induced Cardimentioning
confidence: 99%